Effects of 25-hydroxycholecalciferol supplementation on breast meat quality and histomorphometric characteristics in broiler chickens - Tüzün, Ahmet Engin (Journal of the Hellenic Veterinary Medical Society, 2022)
This experiment was carried out to elucidate the influences of 25-hydroxycholecalciferol status in the diet and gender of the chicken on the sensory and histomorphometric characteristics in breast muscle (Pectoralis major) of broilers. The experiment was a randomized design consisting 2×2 factorial arrangement with 25-hydroxycholecalciferol (3000 and 5000 IU kg/diet) and two gender. Breast weight was not affected by dietary 25-hydroxycholecalciferolstatus and gender of the bird. Cooking loss decreased in females but not in male chickens with additionally 25-Hydroxycholecalciferol supplementation. However, increasing 25-hydroxycholecalciferol level in the diet reduced drip loss in male chickens but no change was observed in females ones. A significant increase in breast meat pH24 was observed with increasing dietary level of 25-Hydroxycholecalciferol; however, squeezable water ratio, lightness (L*), redness (a*) and yellowness (b*) values were comparable in the groups. The histomorphometric characteristics of chicken breast meat throughout the growth period, except for the cross sectional area and number of fibers, were interactively influenced by 25-hydroxycholecalciferol and gender of the bird. In conclusion, an improvement of 25-hydroxycholecalciferol status could be a practical tool to increase chicken breast meat quality with beneficial effects on water holding capacity.